2014
DOI: 10.1371/journal.pone.0085596
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Endemic Nature of Dengue Infections in Guangdong, South China: An Epidemiological, Serological, and Etiological Study from 2005–2011

Abstract: ObjectivesFrequent outbreaks of dengue are considered to be associated with an increased risk for endemicity of the disease. The occurrence of a large number of indigenous dengue cases in consecutive years indicates the possibility of a changing dengue epidemic pattern in Guangdong, China.MethodsTo have a clear understanding of the current dengue epidemic, a retrospective study of epidemiological profile, serological response, and virological features of dengue infections from 2005–2011 was conducted. Case dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 24 publications
4
60
0
3
Order By: Relevance
“…Typically, younger individuals and those aged over 60 years had an increased risk of acquiring a dengue infection in dengue-endemic areas. 13,14 However, in this study, a comparatively higher incidence of infection was observed in adults aged 20–34 years, which suggested that Guangdong province still maintained a low prevalence of DENV and that immunity to DENV was still at low levels in adults, which was consistent with the reports by Guo et al 10 It has also been reported that in southeast Asian countries, DHF is mainly a disease of childhood while in the tropical Americas, all age groups are susceptible. 15,16 However, no DHF cases in children were observed in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Typically, younger individuals and those aged over 60 years had an increased risk of acquiring a dengue infection in dengue-endemic areas. 13,14 However, in this study, a comparatively higher incidence of infection was observed in adults aged 20–34 years, which suggested that Guangdong province still maintained a low prevalence of DENV and that immunity to DENV was still at low levels in adults, which was consistent with the reports by Guo et al 10 It has also been reported that in southeast Asian countries, DHF is mainly a disease of childhood while in the tropical Americas, all age groups are susceptible. 15,16 However, no DHF cases in children were observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…With four serotypes of DENV reported, Guangzhou contains DENV strains of rapidly increasing genetic diversity as imported cases emerge every year. 10 Therefore, scientists have shown concern that a major DENV outbreak may occur in Guangzhou in the near future. In July 2014, a severe outbreak of dengue occurred in Guangzhou, proving the merits of this concern.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of locally acquired cases for which DENV serotype was identified ranged from 11.7% (188 / 1,603 reported cases across Guangdong province) during the relatively low-transmission period from 2005-2011 28 to 0.8% (345 / 45,225 reported cases across Guangdong province) during the large epidemic in 2014 29,32 . As summarized elsewhere 28,29 , DENV-1 appeared to be the dominant serotype in 2005-2011, with reports of the other three serotypes during 2012-2015. Within a given serotype, multiple genotypes were observed across all years and in 2014 in particular 37,38 .…”
Section: Datamentioning
confidence: 99%
“…Observamos uma maior incidência na faixa etária 20 a 39 anos, corroborando os dados encontrados por Guo et al, na China 17 . Entretanto, essa não é a faixa etária que se concentra a maior mortalidade, pois mundialmente o maior risco de morte ocorre em menores de 1 ano 18 , os quais concluíram que a condição socioeconômica não foi preponderante para o risco em adquirir dengue, sendo que há presença da doença também nas regiões centrais, onde se apresentam o menores IEX e melhor condição socioeconômica 18 .…”
Section: Metodologiaunclassified